Permeability Behavior of Tropical Sapric Peat Under Isotropic Compression - Alsidqi, Hasan; Walter Janting, Ngelambai (Springer Nature Switzerland AG, 2024)
Tropical sapric peat originates from highly decomposed woods. It consists of organic particles with colloidal microstructure and jelly-like texture. The complex fabric infuences the permeability and the rate of pore water dissipation. The objective of this paper is to measure the permeability of tropical sapric peat using the fexible wall permeameter procedure. A special preparation method is presented, where each specimen was isotropically compressed under diferent efective stresses using a modifed triaxial apparatus and monitored for 2 days-long permeability tests. The results showed that the permeability decreases with time following a negative power function, indicating gradual progress from the transient to semi-steady states. A graphical method is proposed to separate the transient state and the semi-steady state fow phases and to determine a representative coefcient of permeability. The time taken to achieve the semi-steady state was correlated with the level of compression. There is a good statistical correlation between the coefcient of permeability and the log of efective stress. The tropical sapric peat reported in this study has a lower permeability-to-efective stress ratio when compared to the amorphous sapric peat data from the literature. The fndings of this paper ofer excellent measurements for academic and engineers to better understand the permeability behavior of tropical sapric peat .